Faktor-Faktor Determinan dalam Pencegahan Infeksi pada Proses Persalinan di Puskesmas Pacet - Helvy Helvy (Jurnal Kewidyaiswaraan, 2020)
In the Neonatal Obstetric Service at the Public Health Center, or often abbreviated as Poned. Poned at Pacet Public Health Center in 2016 there were 12 cases of Aids.Midwives as service providers have not yet used Personal Protective Equipment well, 8 out of 10 midwives who have received Normal Childbirth Training (APN) have not shown good behavior in preventing infection. Therefore, it is necessary to know the determinant factors that influence the behavior of midwives in preventing infections including motivation, training, and supervision. These three factors need to be understood to influence the behavior of midwives in the prevention of infection in childbirth at the Pacet Public Health Center.This research uses quantitative methods with analytical research designs. The population in this study were midwives who worked at the Pacet Public Health Center 21 people. Data collection techniques using primary data and secondary data. Secondary data were obtained from the Department of Health and the Pacet Public Health Center, while primary data were distributed by distributing instruments to 21 respondents. Data analysis techniques using SPSS 24 with chi square statistical tests. The results showed that there was no relationship between motivation and midwife behavior in preventing infection with a P value greater than the value of α (0.854> 0.05) and an OR value of 0.786. The results of the second study showed that there was no relationship between training and midwife behavior in preventing infection and the value of α (0.676> 0.05). And the results of the third study showed that there was a relationship between supervision and midwife behavior in preventing infection with a P value smaller than α (0.005 <0.05) and an OR value of 34,000.